Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-27T13:34:53+02:00
A) (x+1)(x+4)=x²+4x+x+4=x²+5x+4
b) 2(2x+3)(2x-1)=2(4x²-2x+6x-3)=2(4x²+4x-3)=8x²+8x-6
c) -(x+7)(x-3)=-(x²-3+7x-21)=-(x²+7x-24)=-x²-7x+24
d)1-(z+5)(z-1)=1-(x²-x+5x-5)=1-(x²+4x-5)=1-x²-4x+5=-x²-4x+6
e) 2k² - (k+3)(2k+4)=2k²-(2k²+4k+6k+12)=2k²-2k²-10k-12=-10k-12
F) -3(a+2b)(a-b)+3a² =-3(a²-ab+2ab-2b²)+3a²=-3a²-2ab+6b²+3a²=-2ab+6b²

:) prosze
2009-09-27T13:57:07+02:00
A) (x+1)=(x+4)
-2x=4-1
-2x=3/:-2
x=-2
b)2(2x+3)=(2x-1)
4x+6=2x-1
2x=-6-1
2x=-6+(-1)
2x=-7/:2
x=-3,5
c)-(x+7)=(x-3)
-x+7=x-3
-2x=-3+(-7)
-2x=-9/:(-2)
x=4,5
d)1-(z+5)=(z-1)
z+4=z-1
z=-4-1
z=-4+(-1)
z=-5
e)2k² - (k+3)(2k+4)
4k-(k+3)=(2k+4)
3k-2k=4-3
k=1
F) -3(a+2b)=(a-b)+3a²
-3a+(-6b)=(a+b)+9a
-3a+a+9a=b+6b
7a=7b